THE MEANING OF FASTING ACCORDING TO PHILOKALIA FATHERS - Ferderiko Budiman; Hendi Wijaya (Jurnal Matetes STT Ebenhaezer, 2023)
The development of technology affects the lives of believers especially in the matter of worship. The covid-19 pandemic has been one of the causes for worship to be carried out virtually. The latest technology of metaverse has given Christian worship a new color. Current, in-broadcast worship is increasingly sophisticated with a metaverse. The rise and use of metaverse in Christian worship raises controversy and requires a theological review of this. The writing method used was that the study used qualitative methods with descriptive analysis and with the approach to literature the article was intended to provide a theological review of worship done through a metaverse, with the objective of getting the reader to take a stand and see the correct use of a metaverse.